2010
DOI: 10.1091/mbc.e10-01-0028
|View full text |Cite
|
Sign up to set email alerts
|

A Gαi–GIV Molecular Complex Binds Epidermal Growth Factor Receptor and Determines Whether Cells Migrate or Proliferate

Abstract: Migrating cells do not proliferate and vice versa, but the mechanism involved remains unknown. Ghosh et al. reveal how this cellular decision is made by showing that a Gαi–GIV molecular complex interacts with EGF receptor and programs growth factor signaling, triggering migration when assembled and favoring mitosis when assembly is prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
309
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(326 citation statements)
references
References 55 publications
17
309
0
Order By: Relevance
“…We have exploited our previous findings on GIV's conserved GEF sequence (8) and its binding sites on the G protein (8,19) to rationally design and characterize specific GIV mutants that impair or enhance its functional coupling to Gαi3 in vitro and in living cells. From the general standpoint, these findings provide insights into how nonreceptor GEFs work, as well as into the role of GIV's GEF function in controlling cell signaling and migration (8,10,13), which is particularly relevant in the context of cancer metastasis (10,17).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We have exploited our previous findings on GIV's conserved GEF sequence (8) and its binding sites on the G protein (8,19) to rationally design and characterize specific GIV mutants that impair or enhance its functional coupling to Gαi3 in vitro and in living cells. From the general standpoint, these findings provide insights into how nonreceptor GEFs work, as well as into the role of GIV's GEF function in controlling cell signaling and migration (8,10,13), which is particularly relevant in the context of cancer metastasis (10,17).…”
Section: Discussionmentioning
confidence: 98%
“…GIV has been previously reported by us (8,14) and others (11,12) to be an enhancer of PI3K-Akt signaling. We previously found that activation of Gαi3 by GIV is required for the efficient activation of Akt upon stimulation of receptor tyrosine kinases (RTKs) (8,10,14,16,19) as well as G-protein-coupled-receptors (GPCRs) (8,19). To further characterize this function, we generated HeLa cell lines stably expressing similar levels of GIV WT or mutants with significantly different GEF activities (Table 1).…”
Section: Activation Of Akt In Response To Different Stimuli Is Highlymentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the canonical pathway, where heterotrimeric G proteins engage exclusively with ligand-activated receptor GPCRs, the non-receptor GIV-GEF engages with a diverse array of receptors, including GPCRs, Integrins and RTKs. 26,30,31 and, thereby, enables transactivation of G proteins in response to a wide variety of stimuli (Fig. 1).…”
mentioning
confidence: 99%